Superelastic SMA U-shaped dampers with self-centering functions - Wang, Bin; Zhu, Songye (Smart materials and structures, 2018)
As high-performance metallic materials, shape memory alloys (SMAs) have been investigated increasingly by the earthquake engineering community in recent years, because of their remarkable self-centering (SC) and energy-dissipating capabilities. This paper systematically presents an experimental study on a novel superelastic SMA U-shaped damper (SMA-UD) with SC function under cyclic loading. The mechanical properties, including strength, SC ability, and energy-dissipating capability with varying loading amplitudes and strain rates are evaluated. Test results show that excellent and stable flag-shaped hysteresis loops are exhibited in multiple loading cycles. Strain rate has a negligible effect on the cyclic behavior of the SMA-UD within the dynamic frequency range of typical interest in earthquake engineering. Furthermore, a numerical investigation is performed to understand the mechanical behavior of the SMA-UD. The numerical model is calibrated against the experimental results with reasonable accuracy. Then, the stress-strain states with different phase transformations are also discussed.